KONTINUITAS MUNÂSABAH PADA TAFSIR AL-QUR’AN DALAM LINTAS GENERASI (Analisis Kitab Tafsir Mafātiḥ Al-Gaib, Nazhm ad-Durar Fî Tanâsub al-Âyât Wa as-Suwar dan Nizhâm al-Qur’ân) - Nailatuz Zulfa; Anna Shofiana (Mafatih, 2021)
Abstract This paper discusses the continuity/development of the munâsabah of the Qur'an. The focus of this research is on the characteristics of reasonable continuity in the Qur’an through Tafsir Mafātīḥ Al-Gaib, Nazhm ad-Durar Fî Tanâsub al-Âyât Wa as-Suwar, Nizhâm al-Qur’ân. This research approach uses descriptive-analytic, with deductive techniques, that is, looking for a variety of literature or references related to munâsabah. The results show that the munâsabah in this modern-contemporary century is no longer as in the classical and medieval centuries. That means there are already additions. Reasonable verses in one surah applied by classical and middle scholars' explain only part of it. In contrast to the reasoning applied by modern-contemporary scholars who have been able to trigger that the whole verse in one letter there is a correlation.